2004
DOI: 10.1176/appi.ajp.161.2.278
|View full text |Cite
|
Sign up to set email alerts
|

Distress and Depression in Men Who Have Sex With Men: The Urban Men’s Health Study

Abstract: Rates of distress and depression are high in men who have sex with men. These high rates have important public health ramifications. The predictors of distress and depression suggest prevention efforts that might be effective when aimed at men who have sex with men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
170
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(188 citation statements)
references
References 43 publications
17
170
0
1
Order By: Relevance
“…Interviews covered a range of social, psychological, and behavioral phenomena related to HIV. Major sections of the survey instrument included questions about the gay community (involvement, services used, attitudes toward) (Barrett & Pollack, 2005), demographic characteristics (Catania et al, 2006), attendance at gay venues ("places where men go to meet and socialize with other men") Woods et al, 2003), sexual behavior (both a "global" and partner-by-partner assessment), sexual development, including the "coming out" process (Barrett, Pollack, & Tilden, 2002), experiences with harassment and violence (including adverse familial events, anti-gay victimization, sexual coercion, and partner violence) (Arreola, Neilands, Pollack, Paul, & Catania, 2005;Greenwood et al, 2002;Relf, Huang, Campbell, & Catania, 2004),sexual problems, depression, and suicidal ideation (Mills et al, 2004;Paul et al, 2002), substance use (Klitzman, Greenberg, Pollack, & Dolezal, 2002;Stall et al, 2001aStall et al, , 2003, HIV testing and serostatus (Osmond et al, 2000;Stall et al, 2001b), and AIDS care-giving.…”
Section: Methodsmentioning
confidence: 99%
“…Interviews covered a range of social, psychological, and behavioral phenomena related to HIV. Major sections of the survey instrument included questions about the gay community (involvement, services used, attitudes toward) (Barrett & Pollack, 2005), demographic characteristics (Catania et al, 2006), attendance at gay venues ("places where men go to meet and socialize with other men") Woods et al, 2003), sexual behavior (both a "global" and partner-by-partner assessment), sexual development, including the "coming out" process (Barrett, Pollack, & Tilden, 2002), experiences with harassment and violence (including adverse familial events, anti-gay victimization, sexual coercion, and partner violence) (Arreola, Neilands, Pollack, Paul, & Catania, 2005;Greenwood et al, 2002;Relf, Huang, Campbell, & Catania, 2004),sexual problems, depression, and suicidal ideation (Mills et al, 2004;Paul et al, 2002), substance use (Klitzman, Greenberg, Pollack, & Dolezal, 2002;Stall et al, 2001aStall et al, , 2003, HIV testing and serostatus (Osmond et al, 2000;Stall et al, 2001b), and AIDS care-giving.…”
Section: Methodsmentioning
confidence: 99%
“…Participants themselves explained the relatively high number of gay people within Buddhism as due to it being less homophobic and more inclusive than other religions, as others have also reported (Schalow, 1992).) The censure of homosexuality in society as a marginalized form of masculinity has been linked to higher rates of mental illness among gay people (Mills et al, 2004). Thus it is possible that gay meditators -and heterosexuals who display qualities seen as feminine, which are also policed by the same censure (Schippers, 2007) -were particularly susceptible to psychological issues, which meditation subsequently uncovered.…”
Section: Recommendations and Limitationsmentioning
confidence: 99%
“…Hence, in spite of the prevalence and impact of syndemic conditions on the health of MSM, synthesis of the evidence has shown that some MSM are resilient, especially in stopping tobacco use, overcoming internalized homonegativity (IH) and avoiding drug use [14,17,31,53]. This suggests that not all MSM who reside in a hostile environment and are exposed to multiple psychosocial health problems and their syndemic effects develop negative health outcomes.…”
Section: Resilience: a Corollary Of Syndemic Theorymentioning
confidence: 99%